Recombinant AroL‐Catalyzed Phosphorylation for the Efficient Synthesis of Shikimic Acid 3‐Phosphate. Issue 8 (11th May 2018) - Schoenenberger, Bernhard; Wszolek, Agata; Meier, Roland; Brundiek, Henrike; Obkircher, Markus; Wohlgemuth, Roland
Abstract : Shikimic acid 3‐phosphate, as a central metabolite of the shikimate pathway, is of high interest as enzyme substrate for 5‐enolpyruvoyl‐shikimate 3‐phosphate synthase, a drug target in infectious diseases and a prime enzyme target for the herbicide glyphosate. As the important substrate shikimic acid 3‐phosphate is only accessible via a chemical multi‐step route, a new straightforward preparative one‐step enzymatic phosphorylation of shikimate using a stable recombinant shikimate kinase has been developed for the selective phosphorylation of shikimate in the 3‐position. Highly active shikimate kinase is produced by straightforward expression of a synthetic aroL gene in Escherichia coli . The time course of the shikimate kinase‐catalyzed phosphorylation is investigated by 1 H‐ and 31 P‐NMR, using the phosphoenolpyruvate/pyruvate kinase system for the regeneration of the ATP cofactor. This enables the development of a quantitative biocatalytic 3‐phosphorylation of shikimic acid. After a standard workup procedure, a good yield of shikimic acid 3‐phosphate, with high HPLC‐ and NMR purity, is obtained. This efficient biocatalytic synthesis of shikimic acid 3‐phosphate is superior to any other method and has been successfully scaled up to multi‐gram scale. Abstract : The central metabolite shikimic acid 3‐phosphate is essential for the shikimate pathway of microorganisms, certain parasites, and plants. In this study, the authors demonstrate a new selective and straightforward preparative one‐step enzymatic phosphorylation of shikimate in the 3‐position using a stable recombinant shikimate kinase. This work on the biocatalytic synthesis of shikimic acid 3‐phosphate, superior to any other method and successfully scaled up to multi‐gram scale, represents a short preparative access for the first time to the key metabolite shikimate‐3‐phosphate, which was not available globally.